The complete chloroplast genome of Ishige okamurae - Wang, Xixi (Mitochondrial DNA B Resour, 2021)
Ishige okamurae plays an important role in marine ecosystem and biological resource utilization. The total length of chloroplast genome was 129,988 bp, containing a large single-copy region (LSC, 77,531 bp), a small single-copy region (SSC, 41,795 bp) and a pair of inverted repeat regions (IRs, 10,662 bp). The circular genome consisted of 101 protein-coding genes, 29 tRNA genes, and six rRNA genes, with a total of 136. Phylogenetic analysis confirmed the position of I. okamurae within the Phaeophyta.